2016
DOI: 10.21014/acta_imeko.v5i2.349
|View full text |Cite
|
Sign up to set email alerts
|

The high official Harkhuf and the inscriptions of his tomb in Aswan (Egypt). An integrated methodological approach.

Abstract: TECH project (Technology for the Egyptian Cultural Heritage) aimed to document an Egyptian monument for Egyptological studies and researches but, at the same time, to check a new methodological approach for conservation, valorisation and enhancement. In particular, the CNR mission focused the attention on the tomb of Harkhuf, a high official of the VI dynasty (XXIII century BC), who led trading and military expeditions into Nubia. The hieroglyphic texts inscribed on the façade of his tomb are very important an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In the case of complex scenes such as hypogea, some examples of the application of these techniques (independently or combined) have recently been described in the literature. Some examples of applications based on CRP are Angelini et al (2016) and Pérez-García et al (2019). In the case of TLS, we highlight studies such as Ahmon (2004), Nabil et al (2013), Lima & Vergauwen (2018) and Echeverria et al (2019.…”
Section: Geomatics Techniques Applied To Archaeological Sitesmentioning
confidence: 99%
“…In the case of complex scenes such as hypogea, some examples of the application of these techniques (independently or combined) have recently been described in the literature. Some examples of applications based on CRP are Angelini et al (2016) and Pérez-García et al (2019). In the case of TLS, we highlight studies such as Ahmon (2004), Nabil et al (2013), Lima & Vergauwen (2018) and Echeverria et al (2019.…”
Section: Geomatics Techniques Applied To Archaeological Sitesmentioning
confidence: 99%
“…the transformation of equirectangular projection into cubic projection, with the support of specific software for the recognition of the correspondences; the acquisition step made in different way (tilting the camera) considering also the poles deformation above all in the indoor spaces. The authors experimented also an innovative procedure with the use of "Virtual Scan" tool by Gexcel [21,22]. The tool is able to collect virtual scan of a subject in virtual space by using different projection systems such as orthographic, cylindrical, spherical and perspective cameras in any virtual position, established by the user.…”
Section: The Texture Mapping Processmentioning
confidence: 99%
“…In this sense, several studies have shown smart solutions based on the use of fisheye lenses (Covas et al, 2015;Perfetti et al, 2017) or low-weight cameras located on masts (Fiorillo et al, 2016;José Luis et al, 2019). In the case of studies of tombs, several applications have been developed using both photogrammetry (Angelini et al, 2016;José Luis et al, 2019) and TLS (Ahmon, 2004;Fernández-Palacios et al, 2013;Nabil et al, 2013;Lima, Vergauwen, 2018;Echeverria et al, 2019). Considering the current possibilities of the geomatic techniques, in this study we describe the method carried out and the results obtained after their application to several funerary complexes (QH31, QH32 and QH33) in the Necropolis of Qubbet el Hawa (Aswan, Egypt).…”
Section: Introductionmentioning
confidence: 99%